The mediation of self-compassion and other constructs: significance in resilience, depression and anxiety among students - Miladinović, Peđa (Engrami, 2020)
Introduction. Contemporary studies suggest present affective and stress related difficulties such as depressivenes, anxiousness and related states among students of different levels and backgrounds of studies [1,2] hardships that might appear later on, during education and professional activities, depending of the duration and mood severity [3], but also different factors that might play potential protective roles during the whole process [4,5].Objective. To examine the mediation effects of variables positive lateral generalization, perceived social support and self-compassion in a relationship between depression and anxiety with resilience.Method. A cross-sectional research was conducted in Serbian speaking area on 147 students (108 females (73,5%) and 39 males (26,5%)) of different courses and levels of education, and six different hypothethical single mediator models were examined between anxiety, depression and resilience with the intercession of three mediators: perceived social support, lateral generalisation and self-compassion.Results. Results indicate a non-significant relationship between anxiety and perceived social support (r=-0.09; p>0.05) so that assumption for mediation analysis was not met for furter examination for this model. Perceived social support did not mediate the relationship between depression and resilience significantly (b=0.02; p >0.05, 95% Bca CI [-0.03, 0.08]) which was also the case for lateral generalization (b=0.03; p>0.05, 95% Bca CI [-0.01, 0.10]) as well as in the case between anxiety and resilience (b=0.02; p>0.05, 95% Bca CI [-0.01, 0.09]), whilst significant mediation effect of self-compassion was observed both in relationship between depression and resilience (b=-0.24 p
Keywords: lateral generalization; cross-sectional study; social support